Pemberdayaan Pasien dan Keluarga Pasien dalam Pencegahan Amputasi Penderita Diabetes di Kecamatan Mulyorejo Kota Surabaya, Jawa Timur - Anggraini Dwi Sensusiati; Budi Suprapti; Marcha Debby Saraswati (Jurnal Pengabdian Pada Masyarakat, 2021)
EMPOWERMENT OF PATIENTS AND PATIENT FAMILIES IN PREVENTION OF AMPUTATION OF DIABETES IN MULYOREJO DISTRICT, SURABAYA CITY, EAST JAVA PROVINCE. The purpose of implementing this community service program is to empower the community, especially patients and families of diabetes patients, to be able to take steps to prevent disability in diabetes due to amputation. The number of people with diabetes who have to undergo amputation is often influenced by the poor knowledge of diabetes, the low adherence to taking medication, and the poor knowledge and ability of patients and their families in performing wound care for diabetics. In addition, the lack of understanding of diabetes drugs causes the patient to experience side effects that can lead to withdrawal or the patient to experience side effects of hypoglycemia which can put the patient in critical condition. The solution to this problem is to empower diabetes patients and their families. They were given education about diabetes, the importance of taking the medication regularly according to doctor's recommendations, and wound care. In addition, they will be trained on how to do proper wound care for diabetes patients. A medication control post-program will be implemented to ensure that patients will take their medication according to the prescribed guidelines. It is hoped that with this program, the community will understand more about diabetes and its complications to avoiding the disabilities due to amputation by diabetics and patients can avoid unwanted side effects.